PENGARUH WAKTU PRA PEMBEKUAN TERHADAP KUALITAS SEMEN BEKU DALAM PENGENCER SPERMAX (The Effect of Pre-Freezing Time on The Quality of Frozen Semen of Landrace Boars in Spermax Diluent) - Dui, Theresia A. A. T.; Nalley, Wilmientje M; Lawa, Alvrado B; Telupere, Franky M S; Hine, Thomas M; Setyani, Ni M P (JURNAL NUKLEUS PETERNAKAN, 2025)
This research aimed to investigate the effect of pre-freezing time on the quality of frozen Landrace boar semen. Semen was collected from four 2-3 year old Landrace boars. The semen was evaluated macroscopically and microscopically. Subsequently, good quality semen was diluted in a basic extender, then subjected to a holding time of 2 hours at 27-28°C. The semen was then centrifuged at 2000 rpm for 15 minutes. The spermatozoa pellet was re-diluted with a Spermax extender, packaged into 0.5 mL straws, and equilibrated for 2 hours at 3-5°C. After equilibration, the straws were frozen by placing them 10 cm above the surface of liquid nitrogen at ±-110°C for durations of 3, 6, 9, and 12 minutes. The straws were then immersed into liquid nitrogen at -196°C. Thawing was performed by immersing the straws into a water bath containing water at 37°C for 30 seconds, followed by evaluation of semen quality. The results showed that pre-freezing time had no significant effect (P>0.05) on semen quality after dilution and equilibration. However, it had a significant effect (P<0.01) on the recovery rate, motility, and viability of spermatozoa after thawing, with the best treatment being 9 minutes. It was concluded that a pre-freezing time of 9 minutes resulted in the highest quality of frozen Landrace boar semen compared to other treatments.